KEGIATAN SIMPAN PINJAM UNTUK KELOMPOK PEREMPUAN DI DESA KELAMANTAN KECAMATAN BENGKALIS TAHUN 2016 - 2017 - Irwansyah Putra; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
In general, women's saving and loan activities are one of the activities in the form of savings and loan, which all members are women. Bengkalis Sub-district as the Capital of Bengkalis Regency in Riau Province has also participated in this activity since 2011. The discovery of 19 groups of users of Savings and Loans Women who are delinquent due to their business traffic jam. It was found that the process of meeting the financing needs of the business or the basic socialization has not been fully realized. This is due to the limited capital or funds available in the Kecamatan Activity Management Unit of Bengkalis, which has an impact on the waiting list of the unaffordable group of prospective Savings and Loans borrowers. The majority of female groups who utilize the Women Savings and Loan Fund are not entirely to be used in improving household economic activities, but the business capital obtained is used for activities that are merciful. The problem in this research is how the implementation of Savings and Loans Activities for Women Groups in Kelamantan Village Bengkalis Subdistrict, and what are the factors - obstacles in the implementation. The purpose of this study is to know the implementation of Savings and Loans Activities for Women Groups in Kelamantan Village Bengkalis District, and the factors - obstacles in the implementation.This research approach using qualitative research method. The location of this research was conducted in Kelamantan Village Bengkalis District Bengkalis Regency. Informant research using purposive sampling technique. Data collection techniques used are observation, interview and documentation. The data obtained will be analyzed by descriptive method using qualitative approach.The results of this study can be concluded that the implementation of Savings and Loans Activities for Women Group in Kelamantan Village Bengkalis District Year 2016-2017, less run well. Weaknesses in the implementation of Savings and Loans Activities for Women Groups in Kelamantan Village Bengkalis Sub-district Year 2016-2017 occurred in the mentoring that has not been emphasized on business development and marketing and coverage of poor households is still relatively small.Keywords: Activity, Save and Borrow Women's Groups